PENGARUH MEDIA COMIC STRIP TERHADAP MINAT BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN BAHASA INDONESIA - Sunusi, Nasrawati; Anis, Muh; Andra Ningsih, Diarti (Universitas Islam Ahmad dahlan, 2023)
This study aims to determine the effect of Comic Strip Media on Students' Learning Interest in Indonesian Language Learning in Class V of Teppoe Private Elementary School. The type of research used in this study is ex post facto which means after the fact, by taking data by survey, ex post facto research. The approach used in this research is quantitative research. The population is all class V students of Teppoe Private Elementary School, totalling 21 people. And the sampling used is a saturated sample. The results of the study based on simple regression analysis that has been carried out through the SPSS version 25 programme, obtained the results of the respondents studied, namely class V of Teppoe Private Elementary School totalling 21 people. It is known that if tcount ≤ ttable then H0 is accepted and Ha is rejected. If tcount ≥ ttable then H0 is rejected and Ha is accepted. Based on the coefficients table that tcount (3.212) > ttable (2.093) and a probability value of 0.005 <0.05 and in the model summary table by looking at R Square = 0.352 or 35.2% so it can be interpreted that significantly the comic strip media variable (X) affects the student learning interest variable (Y) by 35.2%.